Hermite-Hadamard-Fejér Inequalities for Conformable Fractional Integrals via Preinvex Functions - Yousaf Khurshid; Muhammad Adil Khan; Yu-Ming Chu; Zareen Abdulhameed Khan (Journal of Function Spaces)
In this paper, we present a Hermite-Hadamard-Fejér inequality for conformable fractional integrals by using symmetric preinvex functions. We also establish an identity associated with the right hand side of Hermite-Hadamard inequality for preinvex functions; then by using this identity and preinvexity of functions and some well-known inequalities, we find several new Hermite-Hadamard type inequalities for conformal fractional integrals.